Small and internationalised firms competing with Chinese exporters - Klaus S. Friesenbichler; Andreas Reinstaller (Austrian Institute of Economic Research (WIFO), 2022)
The import competition literature suggests that Chinese industrial policies and technological trends have altered the nature of competition with China so that it does not take place on a level playing field anymore. Empirical evidence about firms' reactions in developed economies to competition with China is inconclusive, however. This paper studies how small, highly internationalised and specialised firms react to the growing penetration of Chinese exporters on their markets. We use a sample of Austrian manufacturing companies to explore the impact of increasing competition on changes in corporate strategy. We propose a novel indicator capturing import competition that highly internationalised companies face. We examine how firms adapt their search strategies related to technological capabilities and markets. While the exposure to Chinese competition has been on average relatively low, its impact on diversification choices has been significant. Companies exposed to growing Chinese competition are more likely to diversify their geographic markets, but less likely to diversify their product portfolio or broaden their competence base. These patterns are also reflected by changes in trade data.
Keywords: L20; L60; M16; 330; China; Austria; import competition; strategy; diversification; manufacturing; SME